Efektivitas Game Edukasi Wordwall Berbasis PBL dalam Meningkatkan Kemampuan Penalaran Matematis dan Keaktifan Siswa - Eril Ismail; Nursafitri Amin; Aprisal Aprisal; Reski Amaliyah AR (FKIP Universitas Mataram, 2026)
This study aims to determine the effectiveness of the Wordwall educational game based on Problem Based Learning (PBL) in improving mathematical reasoning ability and student activeness of class VIII at SMP Negeri 2 Sendana. This quantitative study employed a Nonequivalent Control Group Design. Cluster sampling was used to select class VIII A as the experimental class and class VIII B as the control class (n = 22 each). Data were collected through learning observation sheets, student activeness questionnaires, and mathematical reasoning ability tests. Descriptive analysis showed that the experimental class achieved a post-test mean of 74.18 (high category) for mathematical reasoning and 79.41 (very active) for student activeness, while the control class reached 52 (low) and 56.80 (less active) respectively. N-Gain scores confirmed a high improvement in the experimental class (0.63 for reasoning; 0.66 for activeness) compared to low gains in the control class (0.25 and 0.28). Inferential testing via independent sample t-test and MANOVA (Wilks' Lambda) yielded sig = 0.000 < 0.05, leading to rejection of H0. The results of this research indicate that the Wordwall educational game based on PBL is significantly more effective in improving mathematical reasoning ability and student activeness compared to conventional textbook and LKPD instruction.